Launching of the special 100 x 100 URP program for contributing to scientific production: Lanzamiento del programa especial 100 x 100 URP para contribuir a la producción científica - De La Cruz-Vargas, Jhony A. (2021)
Research should be seen as the most appropriate way for the university to invest and allocate resources. Thanks to the vision, work and impetus of the Rector of the Universidad Ricardo Palma, we are pleased to present this special program today.